Impact of Epiretinal Membrane on Optical Coherence Tomography Tools Used for Monitoring Glaucoma - Marco Rocco Pastore; Riccardo Merli; Carmen Dell’Aquila; Lorenzo Belfanti; Marco Franzon; Gabriella Cirigliano; Chiara De Giacinto; Rosa Giglio; Daniele Tognetto (Diagnostics, 2021)
Background: Retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL) measurements can be influenced by many factors including the presence of concomitant retinal diseases. The aim of this study it to assess the impact of epiretinal membrane (ERM) on RNFL and GCL assessment using optical coherence tomography (OCT). Methods: GCL, peripapillary RNFL (pRNFL), and Bruch’s Membrane Opening Minimum Rim Width (BMO-MRW) thicknesses were analysed using an SD-OCT (Spectralis OCT) in eyes with idiopathic ERM and compared with a control group. Results: 161 eyes were included, 73 eyes in the control group and 88 eyes with idiopathic ERM. The pRNFL analysis revealed a statistically significant difference between the two groups in overall and temporal sector thicknesses. For GCL thickness report, the percentage of scans in which the GCL was erroneously segmented by automatic segmentation was assessed for each eye. A statistically significant difference was found in all sectors (p < 0.001), with the exception of external nasal sector. A statistically significant difference (p < 0.001) in the GCL total volume report was found in ERM group compared to the control group. For MRW at BMO analysis, there was no statistically significant difference in MRW thickness in any sector. Conclusion: In eyes with ERM, the GCL and pRNFL analysis seemed affected by the morphological retinal layers’ modification. MRW-BMO did not appear to be directly affected by the presence of ERM.